Pregnancy after bariatric surgeries; best time, gestational, and neonatal outcomes - Ahmed Mahmoud Abdou; Mohamed A. Wasfy; Mohamed Negm; Walid A. Mawla; Loay M. Gertallah; Ahmed Embaby; Ahmed Fathy Gomaa; Ahmed Lotfy Sharaf; Ola A. Harb; Abdel-Razik El-Sayed Abdel-Razik (Middle East Fertility Society Journal, 2023)
Abstract Background Many studies and organizations described bases of pregnancy timing after bariatric surgeries, but there is still a need for uniform scientific evidence for accurate timing. We aimed to assess pregnancy outcomes and neonatal findings by timing of surgery to pregnancy to compare adverse perinatal outcomes among women who underwent bariatric surgery prior to pregnancy with those who had not. Patients and methods We included 200 pregnant females who previously performed different bariatric surgeries. All pregnant females were divided into three groups: early group of patients who were conceived ≤ 12 months from bariatric surgery included 50 patients (25.0%), middle group of patients who were conceived from 12 to 24 months from bariatric surgery included 50 patients (25.0%) and late group of patients who were conceived > 24 months from bariatric surgery included 100 patients (50.0%). Results There is a more liability to preterm deliveries in the early group in comparison with the middle and late group (P = 0.064). Gestational weight gain in the early group was lower than the middle and the late group (P = 0.002). Females in the early group have a more liability to inadequate gestational weight gain in comparison with in the middle and late group P < 0.001). Neonatal birth weight in the early group was significantly lower than the middle and late group P < 0.001). Conclusion We supported recommendations of postponing pregnancy for more than 12 months after performing bariatric surgery which allowed stabilization of maternal weight, allowing adequate gestational weight gain, better fetal and maternal health later on.